Bone Marrow Stromal Cell Regeneration Profile in Treated B-Cell Precursor Acute Lymphoblastic Leukemia Patients: Association with MRD Status and Patient Outcome - Oliveira, Elen; Costa, Elaine S; Ciudad, Juana; Gaipa, Giuseppe; Sedek, Łukasz; Barrena, Susana; Szczepanski, Tomasz; Buracchi, Chiara; Silvestri, Daniela; Siqueira, Patrícia F R; Mello, Fabiana V; Torres, Rafael C; et al. (Cancers, 2022)
For the last two decades, measurable residual disease (MRD) has become one of the most powerful independent prognostic factors in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). However, the effect of therapy on the bone marrow (BM) microenvironment and its potential relationship with the MRD status and disease free survival (DFS) still remain to be investigated. Here we analyzed the distribution of mesenchymal stem cells (MSC) and endothelial cells (EC) in the BM of treated BCP-ALL patients, and its relationship with the BM MRD status and patient outcome. For this purpose, the BM MRD status and EC/MSC regeneration profile were analyzed by multiparameter flow cytometry (MFC) in 16 control BM (10 children; 6 adults) and 1204 BM samples from 347 children and 100 adult BCP-ALL patients studied at diagnosis (129 children; 100 adults) and follow-up (824 childhood samples; 151 adult samples). Patients were grouped into a discovery cohort (116 pediatric BCP-ALL patients; 338 samples) and two validation cohorts (74 pediatric BCP-ALL, 211 samples; and 74 adult BCP-ALL patients; 134 samples). Stromal cells (i.e., EC and MSC) were detected at relatively low frequencies in all control BM (16/16; 100%) and in most BCP-ALL follow-up samples (874/975; 90%), while they were undetected in BCP-ALL BM at diagnosis. In control BM samples, the overall percentage of EC plus MSC was higher in children than adults (p = 0.011), but with a similar EC/MSC ratio in both groups. According to the MRD status similar frequencies of both types of BM stromal cells were detected in BCP-ALL BM studied at different time points during the follow-up. Univariate analysis (including all relevant prognostic factors together with the percentage of stromal cells) performed in the discovery cohort was used to select covariates for a multivariate Cox regression model for predicting patient DFS. Of note, an increased percentage of EC (>32%) within the BCP-ALL BM stromal cell compartment at day +78 of therapy emerged as an independent unfavorable prognostic factor for DFS in childhood BCP-ALL in the discovery cohort—hazard ratio (95% confidence interval) of 2.50 (1−9.66); p = 0.05—together with the BM MRD status (p = 0.031). Further investigation of the predictive value of the combination of these two variables (%EC within stromal cells and MRD status at day +78) allowed classification of BCP-ALL into three risk groups with median DFS of: 3.9, 3.1 and 1.1 years, respectively (p = 0.001). These results were confirmed in two validation cohorts of childhood BCP-ALL (n = 74) (p = 0.001) and adult BCP-ALL (n = 40) (p = 0.004) treated at different centers. In summary, our findings suggest that an imbalanced EC/MSC ratio in BM at day +78 of therapy is associated with a shorter DFS of BCP-ALL patients, independently of their MRD status. Further prospective studies are needed to better understand the pathogenic mechanisms involved.
Keywords: measurable residual disease; bone marrow microenvironment; B-cell precursor acute lymphoblastic leukemia; endothelial cells; multiparameter flow cytometry; stromal cells; mesenchymal stem cells; disease free survival